Investigating the role of miR-152 and miR-130a in Glucose-Stimulated Insulin Secretion - Ofori,Jones (2013)
Investigating the role of miRNAs in Glucose-Stimulated Insulin Secretion MicroRNAs have emerged as important players in many aspects of fundamental biological processes including regulation of pancreatic β-cell functions. Failure in beta cell functions, specifically with regards to glucose-stimulated insulin secretion (GSIS), contributes in the pathogenesis of type-2 diabetes (T2D). Previous studies in a T2D rodent model, Goto-Kakizaki (GK) rat, implicated dysregulated microRNAs as contributing factors in impaired GSIS. Here, we investigated two such miRNAs in two clonal beta cell lines which display diametrically opposite phenotypes: INS1-832/13 which readily responds to glucose stimulation and secretes high amount of insulin and INS1-832/2, which exhibit very low insulin secretion upon glucose stimulation. Quantification of miRNAs using qRT-PCR shows that both miRNAs are up-regulated in INS1-832/2 cells reflecting the findings in the pancreatic islets of T2D model GK rat. Overexpression of both miRNAs in INS1-832/13 cells reduces insulin secretion by down-regulating important metabolic enzymes necessary for β-cell function during GSIS. We conclude that these miRNAs play important roles in cellular functions necessary for insulin secretion. Advisor: Jonathan Esguerra Master´s Degree Project 45 credits in Molecular Biology, Molecular Genetics 2013 Department of Biology, Lund University